The product to sum formulas are used to express the product of sine and cosine functions as a sum. These are derived from the sum and difference formulas of trigonometry. These formulas are very helpful while solving the integrals of trigonometric functions. Let us learn the product to sum formulas along with proofs and examples.

## What AreProduct To Sum Formulas?

The product-to-sum formulas are a set of formulas from trigonometric formulasandas we discussed in the previous section, they are derived from the sum and difference formulas. Here are the productto sum formulas and you can see their derivation below the formulas.

### Product To Sum Formulas

There are 4 product to sum formulas that are widely used as trigonometric identities.

- sin A cos B = (1/2) [ sin (A + B) + sin (A - B) ]
- cos A sin B = (1/2) [ sin (A + B) - sin (A - B) ]
- cos A cos B = (1/2) [ cos (A + B) + cos (A - B) ]
- sin A sin B = (1/2) [ cos (A - B) - cos (A + B) ]

## Product To Sum Formulas Derivation

We will use the sum/difference formulas of trigonometry to derive the product to sum formulas. Let us recall the sum and difference formulas of sin and cosand give some numbers to each of the sum/difference formulas.

sin (A +B) = sin A cos B + cos A sin B ... (1)

sin (A - B) =sin A cos B -cos A sin B ... (2)

cos (A + B) = cos A cos B - sin A sin B... (3)

cos (A -B) = cos A cos B +sin A sin B... (4)

**Deriving the formulasin A cos B = (1/2) [ sin (A + B) + sin (A - B) ]:**

Adding the equations (1) and (2), we get

sin (A + B) + sin (A - B) = 2 sin A cos B

Dividing both sides by 2,

sin A cos B = (1/2) [sin (A + B) + sin (A - B) ]

**Deriving the formula cos A sin B = (1/2) [sin (A +B) -sin (A - B) ]:**

Subtracting (2) from (1),

sin (A + B) -sin (A - B) = 2 cos A sin B

Dividing both sides by 2,

cos A sin B = (1/2) [sin (A + B) -sin (A - B) ]

**Deriving the formula cos A cos B = (1/2) [cos (A + B) + cos (A - B) ]**

Adding the equations (3) and (4), we get

cos (A + B) + cos (A - B) = 2 cos A cos B

Dividing both sides by 2,

cos A cos B = (1/2) [ cos (A + B) + cos (A - B) ]

**Deriving the formula sin A sin B = (1/2) [cos (A -B) -cos (A +B) ]**

Subtracting (3) from (4),

cos (A - B) - cos (A + B) = 2 sin A sin B

Dividing both sides by 2,

sin A sin B = (1/2) [ cos (A - B) - cos (A + B) ]

Have questions on basic mathematical concepts?

Become a problem-solving champ using logic, not rules. Learn the why behind math with our certified experts

Book a Free Trial Class

You can see the applications of product to sum formulas in the section below.

## Examples onProduct To Sum Formulas

**Example 1:**Find the value of sin 75^{o}sin 15^{o}without actually evaluating the values of sin 75^{o}and sin 15^{o}.

**Solution:**

Using one of the product to sum formulas,

sin A sin B = (1/2) [ cos (A - B) - cos (A + B) ]

Substitute A = 75^{o}and B = 15^{o}, we get

sin 75^{o}sin 15^{o}= (1/2) [ cos (75^{o}- 15^{o}) - cos (75^{o}+ 15^{o}) ]

= (1/2) [ cos 60^{o}- cos 90^{o}]

= (1/2) [ (1/2) - 0] (from trigonometry table)

= 1/4

**Answer:**sin 75^{o}sin 15^{o}= 1/4.

**Example 2:**Express 2 cos 5xsin 2xas sum/difference.

**Solution:**

Using one of the product to sum formulas,

cos A sin B = (1/2) [sin (A + B) -sin (A - B) ]

Substitute A = 5x and B = 2x in the above formula,

cos 5xsin 2x= (1/2) [sin (5x+ 2x) -sin (5x- 2x) ]

cos 5x sin 2x = (1/2) [sin 7x - sin 3x]

Multiply both sides by 2,

2 cos 5x sin 2x = sin 7x - sin 3x

**Answer:**2 cos 5x sin 2x = sin 7x - sin 3x.

**Example 3:**Find the value of the integral∫ sin 3x cos 4x dx.

**Solution:**

Using one of the product to sum formulas,

sin A cos B = (1/2) [sin (A + B) + sin (A - B) ]

Substitute A = 3x and B = 4x on both sides,

sin 3xcos 4x= (1/2) [sin (3x+ 4x) + sin (3x- 4x) ] = (1/2) [ sin 7x - sin x] (because sin (-x) = - sin x).

Now, we will evaluate the given integral using the above value.

∫ sin 3x cos 4x dx =∫(1/2) [ sin 7x - sin x] dx

= (1/2) [ -cos (7x) / 7 + cos x] + C (using integration by substitution)

**Answer:**∫ sin 3x cos 4x dx= (1/2) [ -cos (7x) / 7 + cos x] + C.

## FAQs onProduct To Sum Formulas

### What AreProduct To Sum Formulas?

The product to sum formulas in trigonometry are formulas that are used to convert the product of trigonometric functions into the sum of trigonometric functions. There are 4 important product to sum formulas.

- sin A cos B = (1/2) [ sin (A + B) + sin (A - B) ]
- cos A sin B = (1/2) [ sin (A + B) - sin (A - B) ]
- cos A cos B = (1/2) [ cos (A + B) + cos (A - B) ]
- sin A sin B = (1/2) [ cos (A - B) - cos (A + B) ]

### How To DeriveProduct To Sum Formulas?

The product to sum formulas are derived using the sum and difference formulas which are:

- sin (A +B) = sin A cos B + cos A sin B
- sin (A - B) =sin A cos B -cos A sin B
- cos (A + B) = cos A cos B - sin A sin B
- cos (A -B) = cos A cos B +sin A sin B

By adding or subtracting two of these four formulas, we can derive the product to sum formulas. You can find the detailed proof/derivation of product to sum formulas from the "What AreProduct To Sum Formulas?" section of this page.

### What Are the Applications ofProduct To Sum Formulas?

The product to sum formulas are used to write the product of two trigonometric functions (sin and cos) as the sum. These formulas are hence useful in integration as integrating a sum is pretty easier when compared to integrating a product.

### HowToUseProductToSumFormulas?

Let us recall the product to sum formulas:

- sin A cos B = (1/2) [ sin (A + B) + sin (A - B) ]
- cos A sin B = (1/2) [ sin (A + B) - sin (A - B) ]
- cos A cos B = (1/2) [ cos (A + B) + cos (A - B) ]
- sin A sin B = (1/2) [ cos (A - B) - cos (A + B) ]

We can use one of these formulas to find the product of sin and (or) cos as the sum. For example if we have to convert cos 15^{o}sin 45^{o}into the sum, we will just apply the formula 2 from the above list. Then we get:

cos 15^{o}sin 45^{o}= (1/2) [ sin (15^{o}+45^{o}) - sin (15^{o}-45^{o}) ]

= (1/2) [ sin 60^{o}+sin 30^{o}] [because sin (-x) = - sin x]

= (1/2) [ (√3/2) +1/2] (from trigonometry table)

= (√3 +1) / 4